Breast cancer in the United States: current treatment and diagnosis strategies, risk factors and preventive methods - Sobuj, Dipongkar R.; Bhuiyan, M. Rokibul H.; Rashid, Tamanna; Arif, Saiful I.; Rana, M. Rakib R.; Maniruzzaman, M.; Akter, Sabina; Jaman, M. Sadikuj (International Journal Of Community Medicine And Public Health, 2025)
Breast cancer is the most frequently diagnosed cancer in women and remains a leading cause of cancer-related deaths worldwide. Its burden affects women physically, mentally, and socially, making it a major public health concern. The development and outcome of the disease are influenced by several risk factors, including age, family history, genetic alterations, reproductive history, lifestyle behaviors such as physical inactivity, obesity, alcohol use, smoking, and exposure to radiation. In the United States, recent evidence indicates that breast cancer among younger women (ages 20–49) is rising, with variations by race, ethnicity, tumor stage, and hormone receptor status. Younger patients often face worse prognoses than older women. Treatment requires a multidisciplinary approach, guided by tumor biology, stage, and molecular markers. For early-stage disease, breast-conserving surgery with radiotherapy or mastectomy remains the standard, often combined with adjuvant systemic therapy based on nodal involvement, hormone receptor, and HER2 status. In metastatic disease, the focus shifts to prolonging survival and maintaining quality of life. Advances in chemotherapy, radiotherapy, endocrine therapy, targeted therapy, immunotherapy, and gene-based treatments continue to expand options. However, disparities in access and outcomes persist.